Respostas
respondido por:
1
isso representa produto pela diferença.
(a+b)(a-b) = a² - b²
logo:
a² - (1/a)² =
a² - 1/a² ← Resposta.
att: Jhonny
(a+b)(a-b) = a² - b²
logo:
a² - (1/a)² =
a² - 1/a² ← Resposta.
att: Jhonny
respondido por:
2
Você pode utilizar a regra:
(a + b) · (a - b) = a² - b²
--------------------------------------------------
(a + b) · (a - b) = a² - b²
--------------------------------------------------
ProfAmaral:
Obrigado!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás